A review of chronic relapsing inflammatory optic neuropathy - Pushpendra Nath Renjen; Dinesh Mohan Chaudhari; Kamal Ahmad; Shivangi Garg; Anjali Mishra (Apollo Medicine, 2020)
Chronic relapsing inflammatory optic neuropathy (CRION), initially described in 2003, is a form of recurrent optic neuritis (ON) that has relatively good response/dependency to steroid treatment. In demyelinating ON, patients present with periorbital ache and pain elicited by eye movement, which usually begins insidiously and worsens, in synchrony with or preceding a reduction in vision, which deteriorates over days. The etiology of CRION is unknown. However, the excellent response to corticosteroids and the need for immunosuppressive therapy to prevent relapse suggests an immunomediated origin.